Prevalence of Depression and its Associated Factors among Inmates - Mahato, Simran; Devkota, Nishchal; Kafle, Birat Raj; Singh, Matrika; Dahal, Harsha Raj (Journal of Nepal Health Research Council, 2023)
Background: Depression can cause suicidal attempts among prisoners and it is intimidating to speculate the deteriorating mental status of them. Since, there is very limited research on the depression of prisoners in Nepal and as prisoners have rights to health care without any discrimination, this cross-sectional study aimed to assess the prevalence of depression and its associated factors among inmates. Methods: An institute-based cross-sectional study was employed on 352 inmates selected by a systematic random sampling method from July 15 to August 15 2022. Face-to-face interview was conducted using the Centre for Epidemiological Studies Depression Scale (CESD). Data were entered into Epi - data version 3.1 and analysed using SPSS version 17. Results: The prevalence of depression among the inmates was 54.3%. About 4.3% reported suicidal ideation during imprisonment. Depression was significantly associated with previous occupation, drug use, duration of incarceration, number of prisoners per cell, family support, social support and suicidal thought during imprisonment. Conclusions: More than half of the prisoners have depressive symptoms & thus recommended for the confirmatory diagnosis and treatment of mental issues drawing the attention of concerned authorities toward prisoner’s mental health. Keywords: CESD; depression; inmates; Nepal